Indoor Human Wayfinding Performance Using Vertical and Horizontal Signage in Virtual Reality. Issue 6 (7th May 2012) - Vilar, Elisângela; Rebelo, Francisco; Noriega, Paulo
Abstract Disorientation has many costs. It may lead to physical fatigue, stress, and frustration and can also jeopardize people's safety. Designing wayfinding aids to fit people's needs can facilitate their environmental knowledge acquisition and, therefore, improve their wayfinding performance. The scope of this article is human wayfinding in unfamiliar buildings, considering only individual pedestrian movement in an immersive virtual environment. The purpose is to investigate the use of external information at a higher level of awareness (e.g., signage) as a wayfinding aid, as well as the use of immersive virtual reality (VR) to study indoor wayfinding. Fifty‐four volunteers accomplished a wayfinding task (i.e., finding a room from the building's entrance) within a virtual building, employing two types of signage systems (i.e., vertical and horizontal conditions). A neutral condition (no signage) was also considered as a control condition to be used as a baseline. Aside from the success of the wayfinding task (getting to the destination), other performance metrics (distance traveled, time spent, number of pauses, and average speed) were analyzed and compared. Although the differences found are not statistically significant, findings suggest that participants assigned to the horizontal condition traveled smaller distances, spent less time, made fewer pauses, and moved at higher average speed than those assigned to vertical and neutral conditions. Gender‐related differences were found statistically significant only in the average speed variable (females were faster than males). © 2012 Wiley Periodicals, Inc.